2013
DOI: 10.1080/13623699.2013.840819
|View full text |Cite
|
Sign up to set email alerts
|

Too good to be true? An assessment of health system progress in Afghanistan, 2002–2012

Abstract: The bold decision was taken in Afghanistan in 2002 to provide donor-funded public health services by means of contracting-out of predefined health care packages. This study seeks to identify the extent to which progress has been made in public health services provision in the context of broader state-building agendas. The article argues that the provision of public health services was also intended to generate a peace dividend and to legitimize the newly established government. The widely portrayed success of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…The same report states that 2200 midwives had been trained before 2010, with 1000 more to be trained between 2012 and 2014, with further claims that efforts so far have been a success [43]. There is a high attrition rate of health professionals and therefore any estimate of success given in government documents is very likely to be overly optimistic [9]. Hiring female health workers in rural areas has proven extremely difficult [9].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same report states that 2200 midwives had been trained before 2010, with 1000 more to be trained between 2012 and 2014, with further claims that efforts so far have been a success [43]. There is a high attrition rate of health professionals and therefore any estimate of success given in government documents is very likely to be overly optimistic [9]. Hiring female health workers in rural areas has proven extremely difficult [9].…”
Section: Resultsmentioning
confidence: 99%
“…Studies that undertake primary data collection are limited by the security situation so frequently conduct small scale surveys or interviews. Studies that utilise secondary data collection are usually reliant on government data that has come under criticism for lack of plausibility [9]. The overall quality of evidence is therefore taken to be low.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, one of the articles takes a comprehensive view through the use of a case study framework to analyze the impact of the success of health sector reforms during the health sector reconstruction period in Kosovo [63]. Comprehensive studies of health sector reform in general are rarely found even elsewhere, but in general are now needed to document and inform current debates [64-66]. …”
Section: The State Of Researchmentioning
confidence: 99%